PERAN UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES (UNHCR) DALAM MENANGANI PENGUNGSI SUDAN SELATAN PADA MASA PANDEMI COVID-19 DI ETHIOPIA PADA TAHUN 2019 – 2020 - Rahmatika, Zalita; Hapsari, Renitha Dwi (Global and Policy Journal of International Relations, 2021)
COVID-19 is a pandemic that has rapidly spread through the world. This COVID-19 pandemic has crippled the world economy, especially to refugees. Refugees are one of the biggest human problems that happened in the world. Refugees are people fleeing conflict or persecution. Refugees from South Sudan are the largest refugee population in Ethiopia. This refugee problem is a problem that must be addressed immediately because it can be threatening and disrupt people's lives, both refugees and the local community. For this reason, in dealing with South Sudanese refugees in Ethiopia, which is increasing day by day, assistance from international actors requested to assist in dealing with refugee problems, one of which is the United Nations High Commissioner for Refugees (UNHCR). UNHCR, to fulfill its role as an Aid Provider, tries to fulfill its role in accordance with the capabilities and functions of UNHCR itself as an international organization in accordance with the mandate from the United Nations to UNHCR to assist refugees by providing Foreign Aid and Capacity Building. Foreign Aid in the form of Humanitarian Assistance provided in various forms such as giving shelters, food, clean water, health, education, and various other forms of assistance. In assisting to refugees, UNHCR also provides assistance such as protection, shelter, WASH, education, health, food, and nutrition, livelihood and environment as assistance provided to South Sudanese refugees in Ethiopia. Keywords : Refugees, COVID-19, UNHCR, Aid Provider, Humanitarian Assistance, Capacity Building, South Sudan, Ethiopia.COVID-19 adalah pandemi yang telah menyebar dengan cepat ke seluruh dunia. Pandemi COVID-19 ini telah melumpuhkan perekonomian dunia, khususnya para pengungsi. Pengungsi merupakan salah satu masalah kemanusiaan terbesar yang terjadi di dunia. Pengungsi adalah orang yang melarikan diri dari konflik atau penganiayaan. Pengungsi dari Sudan Selatan adalah populasi pengungsi terbesar di Ethiopia. Masalah pengungsi ini merupakan masalah yang harus segera diatasi karena dapat mengancam dan mengganggu kehidupan masyarakat, baik pengungsi maupun masyarakat setempat. Untuk itu, dalam menangani pengungsi Sudan Selatan di Ethiopia yang semakin hari semakin meningkat, bantuan dari aktor internasional diminta untuk membantu menangani masalah pengungsi, salah satunya adalah United Nations High Commissioner for Refugees (UNHCR). UNHCR dalam memenuhi perannya sebagai Aid Provider berusaha memenuhi perannya sesuai dengan kemampuan dan fungsi UNHCR sendiri sebagai organisasi internasional sesuai dengan mandat dari PBB kepada UNHCR untuk membantu pengungsi dengan memberikan bantuan luar negeri dan peningkatan kapasitas. Bantuan luar negeri yang berupa bantuan kemanusiaan yang diberikan dalam berbagai bentuk seperti pemberian tempat tinggal, pangan, air bersih, kesehatan, pendidikan, dan berbagai bentuk bantuan lainnya. Dalam membantu pengungsi, UNHCR juga memberikan bantuan seperti perlindungan, tempat tinggal, WASH, pendidikan, kesehatan, makanan, dan gizi, mata pencaharian dan lingkungan sebagai bantuan yang diberikan kepada pengungsi Sudan Selatan di Ethiopia.Kata kunci : Pengungsi, COVID-19, UNHCR, Aid Provider, bantuan kemanusiaan, peningkatan kapasitas, Sudan Selatan, Ethiopia.  DOI : https://doi.org/10.33005/jgp.v9i1.2667